A Technique for Dissecting the Salivary Glands From the Abdomens of Deer Keds (Diptera: Hippoboscidae: Lipoptena Nitzsch, 1818 and Neolipoptena Bequaert, 1942). Issue 6 (2nd November 2020) - Skvarla, Michael J; Poh, Karen C; Evans, Jesse R; Machtinger, Erika
Abstract: Deer keds (Diptera: Hippoboscidae: Lipoptena Nitzsch, 1818 and Neolipoptena Bequaert, 1942) are hematophagous ectoparasites of cervids that occasionally bite other mammals, including humans. In recent years, a number of arthropod-borne pathogens have been sequenced from deer keds. However, it is unclear if the pathogens are just present in host blood in the gut or if the pathogens are present in other organs (e.g., salivary glands) that would suggest that keds are competent vectors. Like other hippoboscoid flies, deer keds have extensive salivary glands that extend through the thorax and into the abdomen, so simply disarticulating and sequencing the thorax and abdomen separately does not circumvent the issues surrounding whole-body sequencing. Herein, we describe a technique for dissecting the terminal portion of the salivary glands from the abdomen in order to screen the thorax and salivary glands separately from the abdomen for arthropod-borne pathogens.